THE ERRORS OF SEGMENTAL PHONEMES AMONG LIBYANS ENGLISH STUDENTS STUDYING IN SEMARANG CITY, INDONESIA (Universitas Negeri Semarang, 2017)
This study attempts to investigate the errors of segmental phonemes that Libyan English students have when they pronounce English sounds. The participants in the study were fifteen, three females and the rest males, who study in Semarang city, Indonesia, and they were form different majors of master and Doctoral degrees (information system, public health, economic and bio-medic) at Semarang State University and Diponegoro University. The participants have never been to any of the English speaking countries, so they do not have any kind of exposure to a native English environment. The data was collected by two methods; recording test, in order to identify and evaluate the segmental errors, and questionnaire, in order to obtain participants’ perceptions about the expected errors, the reasons behind these errors and how to cope with them. The results showed that the Libyan speakers in this study had errors while they produce consonant clusters and certain English sounds, such as: consonants” /p/ , /v/ , /θ/ , /ð/ , /tʃ/ , /dʒ/ and /ŋ/”, vowels “ /ә/ , /ɛ:/ , /i:/ , /ɑ:/ , /u:/ , /ᴐ:/ and /ɪ/”, and finally diphthongs “/eә/ , /ʊә/ , /әʊ/.” This study also provides some helpful suggestions and recommendation that will reduce future errors regarding English segmental phonemes among Libyan English learners.